Intra-abdominal hypertension assessment based on Near Infra-Red reflectometry: New model and low-cost device. (15th March 2020) - David, Marcelo; Halevi, Netanel; Hirshtal, Elad; Peretz, Aviad; Raviv, Aviad; Pracca, Francisco
Highlights: NIR reflectometry correlates with IAP due to mechanical stress. Oxygenation plays a secondary role in the correlation NIR reflectometry-IAP. Distance between LED and photosensor is optimized by the proposed rule-of-thumb. Abstract: This work describes a simple optical model of the abdominal wall for non-invasive assessment of intra-abdominal pressure during laparoscopy, and the optimized design of a low-cost device for clinical measurements. A pilot run performed on a cadaver of a Sus scrofa domesticus (domestic pig) is case-studied for validation of a proposed rule-of-thumb design. Intra-abdominal hypertension was induced by inflating the abdomen. An inverse correlation between intra-abdominal pressure and Near Infra-Red (NIR) reflectometry measurements verified the model. Previous work claimed that changes in NIR reflectometry, during intra-abdominal hypertension, depended on the oxygenation of the abdominal wall tissues. However, in our work on a cadaver, oxygenation is not relevant; therefore, we conclude that the changes in NIR reflectometry are connected to changes in the thickness and density of the abdominal wall due to hypertension, confirming the proposed rule-of-thumb design for a new device.